ERRORS IN “PROGRESSION” CONCEPT OF MATHEMATICS AMONG X CLASS STUDENTS - Dr.T.Sireesha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
It has been a widely accepted facts that the present learning of Progressions by the pupil is far from being satisfactory. The teachers, due of various reasons are neglecting teaching Progressions. It is seen in almost all the students that they lack adequacy in the knowledge of Progressions, its utility in daily life. A kind of fear, anxiety and hat redness is observed when they have to learn Progressions. The students find difficult to identify the type of Progressions such as arithmetic progression, geometric progression. The pupil get confusion in finding the common difference ‘d’, nth term in A.P and sum of n term in A.P. The students face problems in using the suitable formulas in solving the problems in A.P and G.P. Imagination in theoretical problems is very difficult to the students level. Progressions problems depend on various formulas which gives importance to memory. So from the above discussion it is felt necessary to identify to difficulties faced by the students in learning Progressions.